Pemberdayaan Remaja dalam Upaya Pencegahan Kekerasan Seksual pada Remaja - Masruroh Masruroh; Dewi Setyaningsih; Puspito Panggih Rahayu (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2025)
The phenomenon of sexual violence is increasingly prevalent and constitutes a serious issue in various countries. Sexual violence can affect both women and men, irrespective of age, and may occur in schools, communities, or public spaces. Each year, the incidence of sexual violence among adolescents continues to rise. The escalating cases of sexual harassment among adolescents each year are influenced by several factors, one of which is the inadequate knowledge and attitudes of adolescents. Therefore, it is essential to provide sexual health education to adolescents as a preventive measure against sexual violence. The method employed in this community engagement activity involves interactive participation accompanied by case-based discussions, question-and-answer sessions, as well as discussions conducted in the form of Focus Group Discussions (FGD) and educational sessions. As part of the evaluation process, pre-tests and post-tests related to the educational material will be administered to all participants. The outcomes of this activity indicate that participants have gained benefits, including additional knowledge and understanding regarding sexual violence and its prevention. Thus, aligning with the objective of the activity, it aims to empower the community, especially adolescents, in efforts to prevent sexual violence in their surrounding environment.